Effects of Organophosphate and Pyrethroid Insecticides Mixture on the Haemato-Biochemical and Histological Function of Male Albino Rats (Research in Agriculture Livestock and Fisheries, 2022)
Pesticides have been used to treat agricultural lands since ancient times. The effects of an organophosphate (OP) and pyrethroid combination on the haemato-biochemical and histological functions of male albino rats were investigated. Male albino rats (total 18 rats, 12 are treated and 6 are control) were dermally treated with two organophosphate and pyrethroid combinations for 8 weeks (chlorpyrifos, chlorpyrifos-methyl, and lambda-cyhalothrin). We also looked at organ weights, haematological and histological changes, and clinical symptoms. Except for RBCs, total protein, and haemoglobin, all haematological measures rose in treated rats after 8 weeks. After 4 weeks, Runsave and Lambaphos treatments had RBC counts of 5.02 and 5.15 106/mm3, respectively, compared to 6.1 106/mm3 in the control group. Haemoglobin values for Runsave, Lambaphos, chlorpyrifos, chlorpyrifosmethyl, and lambda-cyhalothrin were 13.53, 14.27, 14.60, 15.03, and 15.27 g/100 ml after toxicant administration, compared to 16.53 in the control. Haematological parameters change correlated positively with exposure time. A histological examination on liver and kidney found that Runsavetreated rats had an uneven structure, severely congested blood arteries, necrotic areas, fatty liver, pyknotic nuclei, and cytoplasmic vacuolation in hepatic cells. Lambaphos-treated liver shows haemolysis, cytoplasmic vacuolation, pyknotic nuclei, and partial structural disruption. Bowman's capsule, glomeruli, and proximal tubule are normal in the control kidney. Runsave had abnormal renal anatomy. Lambaphos kidneys are asymmetrical. This study demonstrated that albino rats subjected to an insecticide mixture of organophosphate and pyrethroid had significant histological and haematobiochemical changes compared to the control group.Vol. 9, No. 2, August 2022: 185-200